(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2016)
Objective: To observe fluid and nutritional management along with specific management and close clinical monitoring without intensive care management improve the condition of unconcious eclamptic patients in the resource poor setting. Method: Six hundred and nine(609) eclamptic patients were admitted in Mymensingh Medical College Hospital from January to December 2008. Twenty four (24) unconscious eclamptic patients were enrolled for this clinical trial study. These patients were managed in eclampsia ward with fluid therapy of 0.9% sodium chloride, 25% glucose, 5% aminoacids along with hydrocortisone and in some cases nasogastric feeding in addition to other regular medications. They were compared with 26 eclampsia patients treated with normal regular hospital management. A systematic guideline was followed and patients were closely monitored until the outcome. Results: The mean age of 23 years, 18 cases were primi-gravida; 16 had intrapartum, 6 had postpartum and 2 had antepartum eclampsia. The mean number of convulsion before admission was 12. The mean Glasgow Coma Scale (GCS) of these patients during admission was 5, which improved to 10.3 in 24 hours and 14.5 in 36 hours. None of these patients had fatal outcome in compare to observation group where three patients died following complications. Conclusion: Close monitoring with fluid and nutritional management can significantly reduce the mortality of unconscious eclamptic patients in resource poor settings where intensive care facility is limited. Development and adaptation of feasible systematic guideline for the management of unconscious eclamptic patient should be scaled up for the resource poor settings of developing and under developed countries. Bangladesh J Obstet Gynaecol, 2012; Vol. 27(1) : 18-20